The art of active listening : how people at work feel heard, valued, and understood - Younger, Heather R. (Berrett-Koehler Publishers, Inc., 2023)
"Leaders can achieve better working relationships, higher loyalty, and higher revenues simply by changing their listening strategy. Organizations are caught up in the Great Resignation because team members have not felt heard for a long time. Even with renewed focus on human resources and DEI initiatives, we aren't hearing each other. Heather Younger says what we need is a new change model for organizational listening. She illustrates five steps in the "cycle of listening": 1. Recognize what's not being said-Pick up important signals, including nonverbal ones, in our environments. 2. Seek to understand-Step outside our own experiences to uncover the needs and perceptions of our colleagues. 3. Decode-Reflect on what we hear to gain a deeper understanding. 4. Act-Apply this understanding to create and communicate a plan of action. 5. Close the loop-Connect the dots between what we hear and what we will do in response. This book will help break our current listening cycles so we can implement one that honors all parties and works for the long haul. Discussion guide is available in the book for reading groups and book clubs"--